2011
DOI: 10.1007/s11858-011-0350-5
|View full text |Cite
|
Sign up to set email alerts
|

A teacher’s learning process in dual design research: learning to scaffold language in a multilingual mathematics classroom

Abstract: In this paper, we argue that dual design research (DDR) is a fruitful way to promote and trace the development of a mathematics teacher's expertise. We address the question of how a teacher participating in dual design research can learn to scaffold students' development of the language required for mathematical learning in multilingual classrooms. Empirical data were collected from two teaching experiments (each with 8 lessons, and 21 and 22 students, aged 11-12 years), for which lesson series about line grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
1
21
0
2
Order By: Relevance
“…Related with the last point and with our theoretical framework, the ability of the teacher to help the child or scaffolding his/her necessities in the learning process is a crucial element (Smit & Van Eerde, 2011).…”
Section: Scaffolding As a Main Vehicle To Allow Practicing Classificamentioning
confidence: 96%
“…Related with the last point and with our theoretical framework, the ability of the teacher to help the child or scaffolding his/her necessities in the learning process is a crucial element (Smit & Van Eerde, 2011).…”
Section: Scaffolding As a Main Vehicle To Allow Practicing Classificamentioning
confidence: 96%
“…To enact this general design principle in the classroom, the teacher was asked to enact scaffolding strategies that were formulated, enacted, and tested in an earlier phase of the design-based research project reported here (Smit and Van Eerde 2011). These strategies involved diagnosis of the quality of the mathematical language used by students and involved responsive actions with the intention to make students independent users of precise language (cf.…”
Section: Scaffolding Strategiesmentioning
confidence: 99%
“…There have also been a number of smaller projects focused on a certain type of communicative method. Smit and van Eerde (2011) focused on the scaffolding process in relation to teaching mathematical terminology; Oliveira (2010a) focused on types of teacher questions in class, the adoption of ways to invite students to share their opinions and articulate their own ideas, and the use of communication to build solidarity or group cohesiveness (Oliveira, 2010b).…”
Section: Teachers As Creators Of Dialogic Teachingmentioning
confidence: 99%
“…It contributes to changing practices while providing teachers with necessary education and support; it can also help to monitor what happens when implementing dialogic teaching methods and help to place the concept of dialogic teaching in the environment of the real classroom where teachers have to face real limits and contradictions (Lefstein, 2010). Smit and van Eerde (2011) say that researchers and practitioners respectfully meet in action research in order to create a new conceptualisation of phenomena that are seen as problematic, which is anchored in actual experience and reflection. This was the aim of our research: to be guides for teachers on their way towards dialogic teaching and to identify forms of teaching that have a positive effect on student learning.…”
mentioning
confidence: 99%